2017
DOI: 10.1590/s1677-5538.ibju.2016.0126
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of UHRF1 gene correlates with the major clinicopathological parameters in urinary bladder cancer

Abstract: Introduction Recently, expression of the UHRF1 gene was found to be up-regulated in numerous neoplasms, including the urinary bladder transitional cell carcinoma (TCC).Objective The aim of our study was to determine if the expression levels of UHRF1 gene correlates with the major pathological characteristics of the tumor and patients’ clinical outcome.Materials and Methods In our study, we have analyzed the tissue samples derived from group of 70 patients with histologically confirmed TCC of the urinary bladde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…In gallbladder cancer, UHRF1 depletion is associated with cell apoptosis and cell cycle arrest [ 19 ]. UHRF1 expression enhances in nasopharyngeal carcinoma tissues and acted a tumor inductor in bladder cancer [ 20 ]. In the present study, we have identified that UHRF1 acts as an oncogene in GC.…”
Section: Discussionmentioning
confidence: 99%
“…In gallbladder cancer, UHRF1 depletion is associated with cell apoptosis and cell cycle arrest [ 19 ]. UHRF1 expression enhances in nasopharyngeal carcinoma tissues and acted a tumor inductor in bladder cancer [ 20 ]. In the present study, we have identified that UHRF1 acts as an oncogene in GC.…”
Section: Discussionmentioning
confidence: 99%
“…Due to overexpression in various types of cancers such as gastric cancer,85 colorectal cancer,86 hepatocellular carcinoma,87 ESCC,48,88 prostate cancer,89,90 bladder cancer,91 breast cancer,92 lung cancer,93,94 melanoma,95 medulloblastoma,96 lymphoblastic leukemia,97 and osteosarcoma 98. UHRF1 appears a potential biomarker and is promising in the target therapy of cancers.…”
Section: Uhrf1 Regulation and Target Therapymentioning
confidence: 99%
“…Other studies reported similar overexpression of UHRF1 in bladder cancers and in invasive cell lines, such as 253J, T24, KU7, along with silencing of tumor suppressor genes e.g ., KISS1 and RGS2 [ 56 , 112 , 113 ]. Altogether, these studies emphasize UHRF1 as an attractive biomarker and therapeutic target for bladder cancers.…”
Section: Uhrf1 Expression In Different Cancersmentioning
confidence: 99%